Agglomeration of fine-sized copper ore in heap leaching through geopolymerization process. (1st December 2020) - Chen, Keqiang; Yin, Wanzhong; Rao, Feng; Wu, Jie; Zhu, Zhanglei; Tang, Yuan
Highlights: Geopolymerization is introduced into the agglomeration operation of fine-sized copper ore. Few binders are effective in the agglomeration of fine-sized copper ore, but geopolymer gel is useful. Agglomerates produced by geopolymerization have characteristics suitable for heap leaching. Abstract: Low-grade copper ore with high fines content is required for agglomeration because of the low permeability of the ore bed during acid heap leaching. However, few binders are effective in keeping agglomerates stable in acidic solution. In this study, the effect of geopolymerization on the particle size, compressive strength, acid resistance, and microstructure of fine-sized copper ore-based agglomerates formed by drum agglomeration was examined. In addition, the performances of the feed, agglomerates, and coarse-grained ore in the column leaching process were examined. The results showed that the agglomerates had a larger particle size after the agglomeration process. Further, the agglomerates had high strength and acid resistance because of the formation of geopolymer gel by the geopolymerization process. Column leaching experiments revealed that the agglomerates had good stability, a looser bed, and better permeability in the column, whereas leaching of the feed in the column was difficult because of the low permeability of the feed. Moreover, the leaching rate of agglomerates formed by geopolymerization was significantly higher than that of the coarse-grained ore. The proposed method for the production of fine-sized copper ore-based agglomerates by geopolymerization has potential application in heap leaching.